2017
DOI: 10.4028/www.scientific.net/msf.899.107
|View full text |Cite
|
Sign up to set email alerts
|

Isoconversional Kinetic Analysis of Pyrolysis of Malt Waste

Abstract: Locally available malt waste or brewers' spent grain, a by-product of brewing industry, was found to be a low cost and promising biomass for pyrolysis. A kinetic studied of pyrolysis of malt waste was investigated by non-isothermal thermogravimetric analyses (TG-DTG), applying slow heating rates, 10, 15, 30 and 50 K/min, and well-defined conditions. Activation energies and Arrhenius exponential factors were inferred by different estimation methods: Kissinger, Ozawa, Starink, K-A-S and. The methods presented en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…A Reparametrized Global Reaction (RGR) Model [16] was employed for the first time to represent the kinetic behavior of MgCl 2 -catalyzed pyrolysis of MW. The kinetic parameters were estimated using the Differential Evolution (DE) algorithm [32,[48][49][50] and then analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Reparametrized Global Reaction (RGR) Model [16] was employed for the first time to represent the kinetic behavior of MgCl 2 -catalyzed pyrolysis of MW. The kinetic parameters were estimated using the Differential Evolution (DE) algorithm [32,[48][49][50] and then analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Silvério et al [32] studied the pyrolysis kinetics of MW using isoconversional methods and reported a global activation energy between 214.78-238.23 kJ mol À 1 . Borel et al [29] produced high added-value compounds from the analytical pyrolysis of MW, such as methoxy-2-propyl acetate, furfural and toluene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cevada é um cereal utilizado principalmente pelas indústrias cervejeiras, na fabricação de malte e ocupa a quinta posição de importância econômica no mundo (Silvério et al, 2017). Uma aplicação do resíduo de cevada, que vem sendo cada vez mais explorada, é como suplemento alimentar de bovinos, uma vez que estes resíduos possuem alto valor proteico.…”
Section: Introductionunclassified